Evaluation of hepatoprotective effects of Boesenbergia Rotunda and Curcuma Longa rhizomes extracts in thioacetamide-induced liver damage in rats / Suzy Munir Salama Fanous - Suzy Munir, Salama Fanous (2013)
Researchers focused on developing traditional therapies as pharmacological medicines to treat liver cirrhosis that is accompanied by abnormality in liver functions. This study evaluated the mechanisms of hepatoprotective activity of Boesenbergia rotunda and Curcuma longa rhizome ethanolic extract on liver damage induced by thioacetamide in rats. The crude extracts of Boesenbergia rotunda and Curcuma longa were tested for acute toxicity and antioxidant properties evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH), the antioxidant power of reducing iron (FRAP) and total phenolic content (TPC) The hepatoprotective effect of the plant extracts was evaluated in a rat model of thioacetamide-induced liver damage over 8 weeks. Male Sprague Dawley rats were intraperitonealy injected with 200 mg/kg thioacetamide (TAA) 3 times/week for 8 weeks and daily oral administration of 250 mg/kg and 500 mg/kg for 8 weeks. Silymarin was used as a reference drug that was orally administered to the animals at a daily dose of 50 mg/kg. At the end of the 8 weeks, liver damage was evaluated by weight changes, liver gross and histopathology and biochemical measurements of liver parameters, (AP, ALT, AST, GGT and LDH), prothrombin time ratio, total protein, albumin and bilirubin and lipid profile. The degree of liver fibrosis was measured by Masson’s Trichrome staining. Hepatic cytochrome P450 2E1, Matrix metalloproteinase (MMP-2 and MMP 9) and tissue inhibitor of metalloproteinase (TIMP-1) were measured. Serum levels of transforming growth factor TGF-β1, nuclear transcription factor NF-ĸB, pro-inflammatory cytokine IL-6 and caspase-3 were evaluated. Stress due to oxidation was evaluated by liver malondialdehyde, nitrotyrosine and urinary hydroxyl deoxyguanosine levels. The hepatoprotective activity of B. rotunda and C. longa extracts was evaluated through the liver level of antioxidant iii enzymes superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx). Protein expression of pro-apoptotic Bax and anti-apoptotic Bcl-2 proteins in the animal blood sera was determined and confirmed by immunohistochemistry of Bax, Bcl-2 proteins and proliferating cell nuclear antigen (PCNA). Panduratin A and Germacrone compounds of B. rotunda and C. longa rhizomes respectively were tested for their cytotoxicity and protective activity against TAA-induced oxidative damage in embryonic normal liver cell line WRL-68. The compounds were isolated from the ethanolic crude extracts by Column chromatography, thin layer chromatography and high performance liquid chromatography and their mass was determined by Liquid Chromatography Mass Spectrometry (LCMS) (m/z = 407.22 for Panduratin A and 219.17 for Germacrone). The hepatoprotective activity of the isolated Panduratin A was evaluated in vivo in a similar rat model for a period of 4 weeks using 3 different doses 5, 10 and 50 mg/kg. The effect of Panduratin A on hepatic stellate cells (HSCs) activity was measured by alpha-smooth muscle actin staining. B. rotunda and C. longa treatment improved liver histopathology, immunohistochemistry and biochemistry, triggered apoptosis, inhibited serum cytokines, extracellulat matrix proteins and hepatocytes proliferation, but C. longa had no impact on hepatic CYP2E1, MMP-2 or TIMP-1 levels. Moreover, Panduratin A showed significant improvement in the liver biochemistry, histopathology and inhibited HSCs activity. The development of liver fibrosis can be attenuated by the antioxidant and anti-inflammatory activities of C. longa and B. rotunda ethanolic extracts and its active compound Panduratin A while the normal status of the liver can be preserved.